2011
DOI: 10.1007/s10518-011-9296-9
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake insurance portfolio analysis of wood-frame houses in south-western British Columbia, Canada

Abstract: Earthquake disasters affect many structures and infrastructure simultaneously and collectively, and cause tremendous tangible and intangible loss. In particular, catastrophic earthquakes impose tremendous financial stress on insurers who underwrite earthquake insurance policies in a seismic region, resulting in possible insolvency. This study develops a stochastic net worth model of an insurer undertaking both ordinary risk and catastrophic earthquake risk, and evaluates its solvency and operability under cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The HAZUS framework is specifically useful to preand post-disaster activity managements but it does not provide the probability distribution of the aggregated losses required, for example, by the insurance/re-insurance industry. In the last decade, many studies were dedicated to developing and enhancing the accuracy of portfolio loss estimation accounting for different aspects of the problem dealing with uncertainty treatment, spatially correlated ground motions, stochastic modeling, geographical aggregation of assets in a portfolio and generation of fragility and vulnerability functions (Aslani et al 2012;Bazzurro and Luco 2005;Bazzurro and Park 2007;Goda and Yoshikawa 2012;Silva 2017;Silva et al 2015;Villar-Vega et al 2017;Weatherill et al 2015). Most of these advancements took place in the private sector where catastrophe risk modelers responsible for estimating earthquake risk have generated new sophisticated tools and techniques in the field of catastrophe risk modeling and urban/regional seismic risk assessment.…”
Section: Overview Of Our Seismic Risk Assessment Approachmentioning
confidence: 99%
“…The HAZUS framework is specifically useful to preand post-disaster activity managements but it does not provide the probability distribution of the aggregated losses required, for example, by the insurance/re-insurance industry. In the last decade, many studies were dedicated to developing and enhancing the accuracy of portfolio loss estimation accounting for different aspects of the problem dealing with uncertainty treatment, spatially correlated ground motions, stochastic modeling, geographical aggregation of assets in a portfolio and generation of fragility and vulnerability functions (Aslani et al 2012;Bazzurro and Luco 2005;Bazzurro and Park 2007;Goda and Yoshikawa 2012;Silva 2017;Silva et al 2015;Villar-Vega et al 2017;Weatherill et al 2015). Most of these advancements took place in the private sector where catastrophe risk modelers responsible for estimating earthquake risk have generated new sophisticated tools and techniques in the field of catastrophe risk modeling and urban/regional seismic risk assessment.…”
Section: Overview Of Our Seismic Risk Assessment Approachmentioning
confidence: 99%
“…Important requirements for a viable PBEE methodology are that key variables, such as earthquake scenario (EQS), ground motion, nonlinear structural response, damage severity, and economic loss, are modeled comprehensively and that their uncertainty and dependency are propagated consistently through probabilistic calculus. The output facilitates the informed decision making related to seismic risk mitigation (Goda and Hong, ; Porter et al., ; Goulet et al., ) and financial risk management of insurance portfolios (Goda and Yoshikawa, ). Recent major advances of the methodology include the incorporation of spatially correlated ground motion measures (Goda and Hong, ) and the consideration of interdependency of complex infrastructure systems (Adachi and Ellingwood, ; Hernandez鈥怓ajardo and Duenas鈥怬sorio, ).…”
Section: Introductionmentioning
confidence: 99%
“…The procedure for designing a SI鈥恇ased trigger mechanism for multiple鈥恉iscrete payments is demonstrated using a realistic example of conventional wood鈥恌rame houses in Vancouver, Canada (Goda et al., ). Moreover, various CAT bond arrangements and reinsurance coverage will be considered to show how an overall seismic loss curve for a portfolio can be manipulated by risk transfer tools in terms of risk metrics, such as value at risk (VaR), tail value at risk (TVaR), and ruin probability (Artzner et al., ; Barg猫s et al., ; Goda and Yoshikawa, ). It is worth noting that comprehensive evaluation of the new risk transfer instruments in the context of financial earthquake risk management (i.e., comparison of seismic loss curves and risk metrics) is critically lacking in the literature and this study is a novel contribution.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, there is an urgent research need to further develop more rigorous tools/methods that can be used for complex risk management problems. One such problem is insurance/reinsurance portfolio analysis of properties protected by earthquake insurance (Dong and Grossi, 2005;Kleindorfer et al, 2005;Bazzurro and Park, 2007;Goda and Yoshikawa, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…In particular, a model that fi ts the major part of small loss data well may not be suitable for describing the upper tail of large loss data, which is of greater importance for insurers and reinsurers. A recent study by Goda and Yoshikawa (2012) demonstrated that physical effects of spatially correlated ground motions affect the insurer's ruin probability; adequate portfolio management strategies must be sought to meet regulatory requirements for stable operation, depending on reserve fund, characteristics of business related to non-catastrophic risks, and insurance arrangements.…”
Section: Introductionmentioning
confidence: 99%